The perception of students and teachers about the teaching and learning of the straight circular cylinder (Research, Society and Development, 2020)
This work aimed to map the difficulties found in the teaching and learning of cylinder. To this end, a literature review on the teaching of spatial geometry was carried out. Subsequently, two questionnaires were applied, one for students graduating in the subject and another for basic education teachers. To obtain the total sample, the convenience sampling technique was used, which totaled a sample of 100 students from the 2nd year and the 3rd year of high school and 41 teachers. Data analysis was carried out through microgenetic analysis and discourse analysis, which validated the experiment carried out, as they pointed out as a result the evidence of learning present between students and teachers participating in the experiment. It was concluded that the referred content is approached in a “traditional” way, in which most teachers “present the concepts, examples, solved exercises and exercises proposed in the textbook”, in addition to “elaborating a list of exercises or handout for be solved by the students ”to fix the content, and generally evaluate the students through “tests”.